Effects of pH and Oxidants on the First Steps of Polydopamine Formation: A Thermodynamic Approach - Salomäki, Mikko; Marttila, Lauri; Kivelä, Henri; Ouvinen, Tuomo; Lukkari, Jukka (The journal of physical chemistry. B, 2018)
We present a general thermodynamic top-down analysis of the effects of oxidants and pH on dopamine oxidation and cyclization, supplemented with UV–vis and electrochemical studies. The model is applicable to other catecholamines and various experimental conditions. The results show that the decisive physicochemical parameters in autoxidation are the pK values of the semiquinone and the amino group in the oxidized quinone. Addition of Ce(IV) or Fe(III) enhances dopamine oxidation in acidic media in aerobic and anaerobic conditions by the direct oxidation of dopamine and, in the presence of oxygen, also by the autoxidation of the formed semiquinone. At pH 4.5, the enhancement of the one-electron oxidation of dopamine explains the overall reaction enhancement, but at a lower pH, cyclization becomes rate-determining. Oxidation by Cu(II) at reasonable rates requires the presence of oxygen or chloride ions.